Der ägyptische bürgerliche Kalender: Forschungsstand, Probleme und Perspektiven - Quack, Joachim Friedrich (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2018)
[The Egyptian civil calendar comprised 365 days, organized in 12 months, each of 30 days, plus 5 additional days. These so-called “epagomenal” days are attested as soon as there is any clear evidence for the calendrical structure at all. There is no reason to suppose that previously to the attested state, there had been a structure with simply 12 months and only 360 days. Different models are possible for how the Egyptians arrived at the closest possible approximation to the length of the astronomical year, but none proposed so far is really compelling. With some probability, the Egyptian civil calendar was taken over by the Persians; this model is still used nowadays within the religious communities of the Zoroastrians and the Mandaeans.]